Single stage converters for low power stand-alone and grid-connected PV systems - Junior, Luigi G. [UNESP]; De Brito, Moacyr A.G. [UNESP]; Sampaio, Leonardo P. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This work presents the evaluation of different power electronic integrated converters suitable for photovoltaic applications, in order to reduce complexity and improve reliability. The rated voltages available in Photovoltaic (PV) modules have usually low values for applications such as regulated output voltages in stand-alone or grid-connected configurations. In these cases, a boost stage or a transformer will be necessary. Transformers have low efficiencies, heavy weights and have been used only when galvanic isolation is mandatory. Furthermore, high-frequency transformers increase the converter complexity. Therefore, the most usual topologies use a boost stage and one inverter stage cascaded. However, the complexity, size, weight, cost and lifetime might be improved considering the integration of both stages. In this context, some integrated converters are analyzed and compared in this paper in order to support future evaluations and trends for low power single-phase inverters for PV systems. Power decoupling, MPPT and Tri-State modulations are also considered. Finally, simulation and experimental results are presented and compared for the analyzed topologies. © 2011 IEEE.
Keywords: Galvanic isolation; Grid connected PV system; Grid-connected; Integrated converters; Inverter stage; Low Power; Output voltages; Photovoltaic applications; Photovoltaic modules; PV system; Rated voltages; Single stage converters; Single-phase inverters; High frequency transformers; Industrial electronics; Integration; Topology; Photovoltaic effects